2015
DOI: 10.1080/15548627.2015.1063768
|View full text |Cite
|
Sign up to set email alerts
|

Repetitive stimulation of autophagy-lysosome machinery by intermittent fasting preconditions the myocardium to ischemia-reperfusion injury

Abstract: (2015) Repetitive stimulation of autophagy-lysosome machinery by intermittent fasting preconditions the myocardium to ischemiareperfusion injury, Autophagy, 11:9, 1537-1560, DOI: 10.1080/15548627.2015 Keywords: autophagy, fasting, ischemia-reperfusion, lysosome, myocardial infarctionAbbreviations: CMA, chaperone-mediated autophagy; CQ, chloroquine; GFP, green fluorescent protein; LAD, left anterior descending; LAMP2, lysosomal-associated membrane protein 2; MOI, multiplicity of infection; NRCMs, neonatal rat … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
128
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 161 publications
(137 citation statements)
references
References 83 publications
7
128
0
2
Order By: Relevance
“…Post-MI longitudinal echocardiographic analyses showed that left ventricular remodeling and infarct expansion occurred in rats on the ad libitum diet, but not in those on the ADF diet. Similar to rats, ADF protected the mouse heart against Mi-induced damage (Godar et al, 2015). In contrast to wild type mice, ADF did not protect the hearts of mice with impaired autophagy (Lamp2 heterozygous mutant mice).…”
Section: If and Health Indicators In Laboratory Animalsmentioning
confidence: 99%
“…Post-MI longitudinal echocardiographic analyses showed that left ventricular remodeling and infarct expansion occurred in rats on the ad libitum diet, but not in those on the ADF diet. Similar to rats, ADF protected the mouse heart against Mi-induced damage (Godar et al, 2015). In contrast to wild type mice, ADF did not protect the hearts of mice with impaired autophagy (Lamp2 heterozygous mutant mice).…”
Section: If and Health Indicators In Laboratory Animalsmentioning
confidence: 99%
“…Activation of autophagy, possibly due to de-repression upon reduced insulin/IGF-1/mTORC1 signaling, is another common theme in protection. For example, in a mouse model of myocardial IRI, alternate day fasting for 6 weeks protected the myocardium through the transcriptional activation of autophagy, resulting in a reduced infarct size (Godar et al, 2015). Autophagy has also been shown to provide organ protection in the context of renal IRI (Jiang et al, 2010), while the mTORC1 repressor Tsc1 confers neuroprotection in a model of acute ischemic stroke by inducing autophagy (Papadakis et al, 2013).…”
Section: Dietary Preconditioning Against Surgical Stressmentioning
confidence: 99%
“…Lipid peroxidation, reactive oxygen species (ROS) production, apoptosis, and DNA/RNA injury are reported to be associated with MI/RI [3]. If these factors are not purged, they may ultimately induce a high incidence of chronic heart failure [4][5][6]. Hence an increasing number of cardiologists are interested in the strategies to reduce MI/RI, including medical treatment, surgical intervention, and gene therapy [7][8][9].…”
Section: Introductionmentioning
confidence: 99%